Oligomerization, transport, and Golgi retention of Punta Toro virus glycoproteins. - Chen, S Y (1991)
We have investigated the oligomerization and intracellular transport of the membrane glycoproteins of Punta Toro virus, a member of the Phlebovirus genus of the family Bunyaviridae, which is assembled by budding in the Golgi complex. By using one- or two-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis, chemical cross-linking, and sucrose gradient centrifugation, we found that the majority of the G1 and G2 glycoproteins are assembled into noncovalently linked G1-G2 heterodimers. At the same time, a fraction of the G2 protein, possibly produced independently of the G1 protein, is assembled into G2 homodimers. Kinetic analysis indicates that heterodimerization occurs between newly synthesized G1 and G2 within 3 min after protein synthesis, and that the G1 and G2 glycoproteins are associated as dimeric forms both during transport and after accumulation in the Golgi complex. Analysis of a G1-truncated G2 mutant, which is also targeted to the Golgi complex, showed that these molecules also assemble into dimeric forms, which are linked by disulfide bonds. Both the G1-G2 heterodimer and the G2 homodimer were found to be able to exit from the endoplasmic reticulum. Differences in transport kinetics observed for the G1 and G2 proteins may be due to the differences in the transport efficiency between the G1-G2 heterodimer and the G2 homodimer from the endoplasmic reticulum to the Golgi complex. These and previous results (S.-Y. Chen, Y. Matsuoka, and R.W. Compans, Virology 183:351-365, 1991) suggest that Golgi retention of the G2 homodimer occurs by association with the G1-G2 heterodimer, whereas the Golgi targeting of the G1-G2 heterodimer occurs by a specific retention mechanism.